Successful thrombolysis for acute ischemic stroke in the presence of hyposphagma: a clinical case report - Ulianskaitė , G.; Timinskaitė , A.; Valaikienė , J. (Neurologijos seminarai, 2020)
Background. In cases with standard indications and contraindications for the treatment of acute stroke, urgent thrombolysis with intravenous tissue plasminogen activator provides undoubted benefit. However, atypical situations not described in standard treatment guidelines may occur in daily clinical practice. Hence, a clinical case of a patient with an acute ischemic stroke and concomitant ocular bleeding is presented. The medical team needed to urgently evaluate the additional risk of ocular bleeding and make the most appropriate decision on using thrombolytic stroke therapy. Case presentation. A 70-year-old female with acute right-sided weakness was admitted to the emergency department within 2.5 hours. Cerebral computed tomography revealed hyperacute ischemia in the left frontal-parietal area. The neurologist diagnosed an acute ischemic stroke in the left middle cerebral artery with mild right-sided hemiparesis, and the ophthalmologist diagnosed subconjunctival haemorrhage (i.e. hyposphagma). In the absence of absolute contraindications, intravenous thrombolysis with tissue plasminogen activator was performed. The neurological symptoms regressed within one day and the hyposphagma was significantly reabsorbed within three days. The patient was discharged without residual deficits. Conclusions. The presented clinical case contributes to the positive evidence that systemic thrombolysis is a safe and effective method for the treatment of an acute ischemic stroke in the presence of hyposphagma.